Resilience in the university context, a mixed exploratory study Roman - Monzón Pinglo, Luis Alberto; Dávila Cisneros, Juan Diego; Rodríguez Torres, Esteban; Pérez Gamboa, Alfredo Javier; Monzón Pinglo, Luis Alberto; Dávila Cisneros, Juan Diego; Rodríguez Torres, Esteban; Pérez Gamboa, Alfredo Javier; Monzón Pinglo, Luis Alberto; Dávila Cisneros, Juan Diego; Rodríguez Torres, Esteban; Pérez Gamboa, Alfredo Javier (Corporación Universitaria Americana, 2023)
Introduction: Current educational contexts show dissimilar levels that demonstrate how the problems that are present in university students are varied in terms of social and psychological factors. These problems arise due to the demands that increasingly raise their level of difficulty. Hence, the importance of achieving an efficient diagnosis of university students' resilience levels, which facilitates resilient and guiding work in them; Objective: to diagnose resilience levels and pathways for their development in university students of the Natural Sciences Major of the Faculty of Social Historical Sciences and Education at the National University Pedro Ruiz del Gallo; Methodology: a mixed exploratory study was conducted, combining qualitative and quantitative data collection and analysis methods, along with the production of meta-inferences based on the results obtained; Results: the conceptualization of resilience, as well as its presence in discourse and the organizational culture itself, were found to be insufficient; Conclusions: resilience plays a decisive role in today's educational contexts, as it contributes favorably to achieving high levels of problemsolving. Likewise, it promotes effective student development and contributes to the reduction of conditions such as stress that affect university students’ lives.